2018
DOI: 10.1111/liv.14005
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalence of anti‐Hepatitis E antibodies in Austrian patients with autoimmune hepatitis

Abstract: Background & Aims Increasing numbers of autochthonous hepatitis E virus infections have been reported in Europe. Chronic infections have been shown in immune‐compromised patients after solid organ transplantation. Hepatitis E virus might be a possible trigger for autoimmune hepatitis and might cause disease flares or relapses in the further course of disease. Aim of this study was to investigate the presence of hepatitis E virus antibodies and hepatitis E virus RNA, and to analyse their impact on immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 42 publications
2
23
0
2
Order By: Relevance
“…Several studies have assessed the prevalence of anti-HEV IgG antibodies in patients with AIH, which was found to be higher than that of the general local population. [12][13][14] These data raised the question as to whether a past HEV infection could be linked to the development of AIH as has previously been described with HEV and other viral infections. 2,4,5,21,22 In our area, the seroprevalence of HEV has been estimated to range between 7% 8 and 11%, 10 similar to what we found in patients with chronic AIH (10%).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Several studies have assessed the prevalence of anti-HEV IgG antibodies in patients with AIH, which was found to be higher than that of the general local population. [12][13][14] These data raised the question as to whether a past HEV infection could be linked to the development of AIH as has previously been described with HEV and other viral infections. 2,4,5,21,22 In our area, the seroprevalence of HEV has been estimated to range between 7% 8 and 11%, 10 similar to what we found in patients with chronic AIH (10%).…”
Section: Discussionmentioning
confidence: 93%
“…Briefly, patients with chronic AIH (n = 50) were mostly female (33, 66%) with a median age of 47 years (32-61). Laboratory test results at diagnosis were: ALT 652 international units (IU) (IQR: 321-1612), AST 561 IU/L (IQR: 301-1503), total bilirubin 3.1 mg/dL (IQR: 1-9.3) and serum IgG levels 18 g/L (IQR: [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Thirty-three patients (66%) presented positive ANA with a median titre of 1:320 (1:80-1:640), 1 patient had positive anti-LKM (2%), 1 anti-SLA (2%) and 31 (62%) ASMA with a median titre of 1:80 (1:40-1:160).…”
Section: Characteristics Of the Study Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, HEV has been suggested as a potential trigger of AIH by Le Cann et al in 1997 11,12 . Recently, a German and an Austrian study supported this hypothesis by showing a higher anti‐HEV IgG prevalence in AIH patients compared to that in the general population 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HEV has been suggested as a potential trigger of AIH by Le Cann et al in 1997 11,12 . Recently, a German and an Austrian study supported this hypothesis by showing a higher anti‐HEV IgG prevalence in AIH patients compared to that in the general population 12,13 . However, a larger Dutch study showed no significant difference in the anti‐HEV prevalence between AIH patients and the general population; thus, this association remains controversial 14 .…”
Section: Discussionmentioning
confidence: 99%